(untitled) (Global Journal of Management and Business Research, 2017)
The study was aimed at assessing skills possessed by secretaries for effective electronic records management in polytechnics in North-Central, Nigeria. Three research questions guided the study. Two null hypotheses were tested at 0.05 level of significance. The population of the study comprised 366 secretaries in ten polytechnics in North- Central, Nigeria. forty one questionnaire items were developed and validated by two experts.Cronbach Alpha coefficient measure of internal consistency was use to test the reliability value of the instrument. The results of the reliability test were as follows, 0.97, 054, and 0.94.The results of the reliability test yielded a value of 0.82 for the entire items. The Mean and standard deviation were used to answer the three research questions. The z- test and ANOVA were used to test the hypotheses at 0.05 level of significance.